Piano Teaching in Private Music School Under Covid-19 Pandemic Situation in China - Xiao, Yu; Pattananon, Nicha (Asia Pacific Journal of Religions and Cultures, 2024)
The continuous development of Chinese music education cannot be separated from the joint efforts of generations of music educators and musicians. In recent years, the overall goal of music subject teaching that has been fully implemented in China is to "cultivate personal beautiful sentiments, cultivate basic musical abilities, cultivate a love for music and rich musical perception, musical expression ability, and rich musical appreciation ability. Specifically, children’s learning focuses on guiding students to get close to and perceive music. The piano training institutions studied in this article mainly adopt a commercial training model, which uses piano training as a means and aims to make profits, mainly focusing on small and medium-sized enterprises. This article explores the current situation of piano course teaching in off-campus training institutions in the post-pandemic era.